2020
DOI: 10.1073/pnas.2012003117
|View full text |Cite
|
Sign up to set email alerts
|

A thermogenic fat-epithelium cell axis regulates intestinal disease tolerance

Abstract: Disease tolerance, the capacity of tissues to withstand damage caused by a stimulus without a decline in host fitness, varies across tissues, environmental conditions, and physiologic states. While disease tolerance is a known strategy of host defense, its role in noninfectious diseases has been understudied. Here, we provide evidence that a thermogenic fat–epithelial cell axis regulates intestinal disease tolerance during experimental colitis. We find that intestinal disease tolerance is a metabolically expen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Notably, adaptive thermogenesis influences immune recruitment and composition in adipose and peripheral tissues, including the liver and gastrointestinal tract [ 145 147 ]. Modulating thermogenic programs, such as by increasing housing temperature to the thermoneutral zone, can alter phenotypes driven by obesity-induced inflammation, atherosclerosis, bacterial sepsis, nonalcoholic fatty liver disease, colitis and cancer [ 145 , 147 , 148 ] to those more consistently observed in human physiology.…”
Section: Controversies and Open Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, adaptive thermogenesis influences immune recruitment and composition in adipose and peripheral tissues, including the liver and gastrointestinal tract [ 145 147 ]. Modulating thermogenic programs, such as by increasing housing temperature to the thermoneutral zone, can alter phenotypes driven by obesity-induced inflammation, atherosclerosis, bacterial sepsis, nonalcoholic fatty liver disease, colitis and cancer [ 145 , 147 , 148 ] to those more consistently observed in human physiology.…”
Section: Controversies and Open Questionsmentioning
confidence: 99%
“…Notably, adaptive thermogenesis influences immune recruitment and composition in adipose and peripheral tissues, including the liver and gastrointestinal tract [ 145 147 ]. Modulating thermogenic programs, such as by increasing housing temperature to the thermoneutral zone, can alter phenotypes driven by obesity-induced inflammation, atherosclerosis, bacterial sepsis, nonalcoholic fatty liver disease, colitis and cancer [ 145 , 147 , 148 ] to those more consistently observed in human physiology. Normal vivarium conditions impose significant thermal stress on experimental animals, which can obscure experimental results and represent an additional obstacle for predictive modeling of human diseases and therapies, as humans spend most of their lives under thermoneutral conditions [ 149 ].…”
Section: Controversies and Open Questionsmentioning
confidence: 99%
“…Besides, the underlying mechanism is mediated by an unexpected crosstalk between thermogenic adipocytes and intestinal epithelial cells. 339 In addition, more direct evidence has shown that the expression of UCP1 is significantly associated with better overall survival of CRC in a cohort study. 340 Furthermore, a signature consisting of six biomarkers, including UCP1, signal transducer and activator of transcription 1 (STAT1), p-cofilin, LIM domain kinase 2 (LIMK2), the Forkhead transcription factor family member 3 (FOXP3), and inducible co-stimulator (ICOS), was identified as the best combination in terms of prognostic power.…”
Section: The Developmental Origin and Anatomical Location Of Thermoge...mentioning
confidence: 99%
“…In addition, BAT also plays a role in regulating intestinal disease tolerance. The BAT transcriptome is dramatically altered in the early and late stages of dextran-sodium sulfate (DSS)-induced colitis in mice without inhibiting the oxygen consumption rate under hypothermic conditions, thus suggesting that BAT responds dynamically to DSS-induced colonic injury and demonstrated the existence of a signaling axis between thermogenic adipocytes and intestinal epithelial cells, which regulates disease tolerance 120 . One study performed nuclear imaging of the BAT activity coupled in subjects and followed the carotid artery anatomy and functional vascular imaging for up to five years, demonstrating that an increased BAT activity may potentially reduce the incidence of subclinical atherosclerosis and improve vascular function rather than increase the risk of CVD 121 .…”
Section: Effects Of the Thermogenic Adipose Tissue On Obesity-related...mentioning
confidence: 99%